David Harvey: Dispossession or Expropriation? Does capital have an “outside”? / David Harvey: espoliação ou expropriação? Há “lado de fora” do capital? - Fontes, Virgínia (Revista Direito e Práxis, 2017)
DOI:10.1590/2179-8966/2017/30245 Resumo O texto, extraído de livro que defende a categoria de capital-imperialismo para explicar o período contemporâneo (o qual integra teoria do valor e do Estado), propõe um debate, com David Harvey, sobre o conceito de acumulação por espoliação. O artigo defende que a as formas de expropriação não se limitam a um momento "primitivo" mas integram a própria forma de expansão ampliada do capital e do capitalismo. Apresenta uma investigação comparativa entre as formulações presentes na obra de Karl Marx, de Karl Kautsky e de Rosa Luxemburgo, para refletir criticamente sobre os conceitos de "externo/interno", de expropriação e de acumulação capitalista no contexto contemporâneo. Palavras-chave: David harvey; Expropriação; Neoliberalismo; Espoliação; Reprodução ampliada. Abstract he present excerpt is taken from a book that stands for the concept of capital-imperialism in order to explain the contemporary period (which integrates theory of value and the state). It proposes a debate, with David Harvey, on the concept of accumulation by dispossession, arguing that expropriation forms are not limited to a "primitive" moment but they are part of an enlarged form of expansion of capital and capitalism itself. It presents a comparative investigation between the formulations present Karl Marx, Karl Kautsky and Rosa Luxemburg works, to critically reflect on the concepts of "external/internal", as well as expropriation and capitalist accumulation in the contemporary context. Keywords: David harvey; Expropriation; Neoliberalism; Dispossession; Enlarged reproduction.